Physical and mathematical models for space objects breakup and fragmentation in hypervelocity collisions. (November 2020) - Smirnov, N.N.; Kiselev, A.B.; Nazarenko, A.I.; Tyurenkova, V.V.; Usovik, I.V.
Abstract: The paper presents results of analysis of existing mathematical models for orbital debris fragments breakup in high velocity collisions. The breakup models are modified and updated taking into account the latest breakup criteria, experimental data and basic conservation laws. The model examples are analyzed, the criterion is developed for distinguishing fragments, which will stay in orbit after collision event. Highlights: Analysis of mathematical models for orbital debris fragments breakup is presented. The breakup models are modified and updated. Criterion for distinguishing fragments, which will stay in orbit, is developed.